Karangmiri towards Quality Family Village - Mahrus Lutfi Adi Kurniawan; Indanazulfa Qurrota A'yun; Budi Jaya Putra (Jurnal Pengabdian Masyarakat Bestari, 2023)
A quality family village is defined as organizing and strengthening the empowerment of family institutions in all their dimensions. The urgency of transitioning a family planning village into a quality family village is to improve the quality of human, family, and community resources. Concepts in quality villages must have a unified database. The purpose of the database is to map the condition of the area; the most urgent problem conditions are taken into consideration for solutions; the potential that can be maximized; and the importance of changing community behavior in quality family villages. Changing community behavior, which is emphasized in activities, is wise in managing household waste. The service is carried out by the socialization method to the community for changing behavior by the Karangmiri community regarding the importance of household waste management and to Pokja for the database. The result of the service is the creation of a database and increasing public awareness of household waste management.